2021
DOI: 10.1155/2021/2059432
|View full text |Cite|
|
Sign up to set email alerts
|

Audit Data Analysis and Application Based on Correlation Analysis Algorithm

Abstract: Traditional audit data analysis algorithms have many shortcomings, such as the lack of means to mine the hidden audit clues behind the data, the difficulty of finding increasingly hidden cheating techniques caused by the electronic and networked environment, and the inability to solve the quality defects of the audited data. Correlation analysis algorithm in data mining technology is an effective means to obtain knowledge from massive data, which can complete, muffle, clean, and reduce defective data and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A study [ 23 ] reported the incidence of postoperative pancreatitis in patients with biliary tract stones between 1.8 and 7.2%, and one case of pancreatitis in the ERCP group in this study occurred, which was considered to be due to papilledema obstructing the drainage of pancreatic fluid, or it may be due to excessive amount and speed of contrast injection into the pancreatic duct. A study [ 24 ] found that indwelling ENBD drainage significantly reduced the risk of biliary tract infection and postoperative acute pancreatitis. This was confirmed by the medication used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study [ 23 ] reported the incidence of postoperative pancreatitis in patients with biliary tract stones between 1.8 and 7.2%, and one case of pancreatitis in the ERCP group in this study occurred, which was considered to be due to papilledema obstructing the drainage of pancreatic fluid, or it may be due to excessive amount and speed of contrast injection into the pancreatic duct. A study [ 24 ] found that indwelling ENBD drainage significantly reduced the risk of biliary tract infection and postoperative acute pancreatitis. This was confirmed by the medication used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has a 0.0456 s average time overhead, which is less than the 0.1584 s average time overhead of SVM and convolutional neural network. This approach has a much greater classification effectiveness than the other two comparison methods [ 30 ].…”
Section: Experimental Simulation and Analysismentioning
confidence: 99%
“…ere are ten different sorts of music genres included in these 1000 files, each having 100 samples. MPCC is utilised to extract the distinctive characteristics of a music signal in this experiment [33,34]. e frame length is 512, and the number of frames is 2133. e sampling frequency is 48000 Hz, the sample bits are 16, the frame length is 512, and the number of frames is 2133 [33,34].…”
Section: Experimental Environment and Data Setmentioning
confidence: 99%
“…MPCC is utilised to extract the distinctive characteristics of a music signal in this experiment [33,34]. e frame length is 512, and the number of frames is 2133. e sampling frequency is 48000 Hz, the sample bits are 16, the frame length is 512, and the number of frames is 2133 [33,34]. In the stage of extracting Mel frequency cepstrum coefficient, 12 dimensional Mel filter is used, and its frequency index is shown in Table 2.…”
Section: Experimental Environment and Data Setmentioning
confidence: 99%